2016
DOI: 10.2169/internalmedicine.55.6640
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism Improves the Pathological Condition of Nonalcoholic Steatohepatitis: A Case of Nonalcoholic Steatohepatitis with Graves' Disease

Abstract: Abstract3,5,3'-triiodo-L-thyronine regulates the glucose metabolism, lipid metabolism, and hepatic steatosis. Several groups have shown the relationships between hypothyroidism and nonalcoholic fatty liver and hypothyroidism and nonalcoholic steatohepatitis (NASH). However, the effect of hyperthyroidism on NASH has not yet been investigated. We herein report effects of thyroid hormone on the pathological condition of NASH in a patient with NASH complicated by Graves' disease. In our case, the liver enzyme leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
3
7
0
Order By: Relevance
“…Our data showed that the prevalence of NAFLD 11.95% in clinical hyperthyroidism subjects, which was lower than subclinical hyperthyroidism and other thyroid status population. To be consistent of our ndings, a case also reported that hyperthyroidism improved the pathological condition of nonalcoholic steatohepatitis 15 .…”
Section: Discussionsupporting
confidence: 90%
“…Our data showed that the prevalence of NAFLD 11.95% in clinical hyperthyroidism subjects, which was lower than subclinical hyperthyroidism and other thyroid status population. To be consistent of our ndings, a case also reported that hyperthyroidism improved the pathological condition of nonalcoholic steatohepatitis 15 .…”
Section: Discussionsupporting
confidence: 90%
“…In the attempt to clarify the mechanisms underlying the anti-steatotic capacity of T3, some studies on T3-regulated cellular pathways that lead to the generation of free fatty acids from stored lipid droplets in the liver, suggested that TH stimulation of fatty acid β-oxidation is also coupled with induction of hepatic autophagy to deliver fatty acids to mitochondria ( 15 ). With regard to human data, a recent report, presenting an example of a patient with NASH complicated by Graves' disease, indicated that hyperthyroidism may improve the pathological condition of NASH ( 16 ). Besides obesity, NAFLD is also associated with another manifestation of the metabolic syndrome, the insulin resistance ( 17 ).…”
Section: Thyroid Hormone T3 and Liver Diseasementioning
confidence: 99%
“…Adjusting for age or BMI, they found a low TT4 concentration was an independent risk factor for hepatic steatosis in this population-based study (p = 0.0143; p <0.0001). Recently, Miyake et al [10] published a case of NASH with Graves' Disease. They treated the patient with thyroid hormone and considered that hyperthyroidism may be a new way to improve the pathological condition of NASH.…”
Section: The Association Between Sarcopenia and Non-alcoholic Fatty Lmentioning
confidence: 99%